2000
DOI: 10.1507/endocrj.47.763
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Sulfonylurea Treatment and Hyperglycemia Aggravate Disproportionately Elevated Plasma Proinsulin Levels in Patients with Type 2 Diabetes.

Abstract: Abstracts.It is established that disproportionately elevated plasma proinsulin levels occur in patients with Type 2 diabetes. In the present study, multivariate analysis was performed to determine what factors contributed to the disproportionately elevated plasma proinsulin levels in Japanese patients with Type 2 diabetes (n=276). Results from univariate analysis showed that both fasting proinsulin/C-peptide ratio and proinsulin/IRI ratio were approximately 2-fold higher in patients with Type 2 diabetes than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Despite these findings, the proinsulin-to-insulin ratio areas under the curve during the 12-h metabolic profile were similar for both therapies, suggesting that glimepiride did not worsen the previous secretor dysfunction of beta cells, as reported with other sulfonylureas (35). …”
Section: Discussionmentioning
confidence: 72%
“…Despite these findings, the proinsulin-to-insulin ratio areas under the curve during the 12-h metabolic profile were similar for both therapies, suggesting that glimepiride did not worsen the previous secretor dysfunction of beta cells, as reported with other sulfonylureas (35). …”
Section: Discussionmentioning
confidence: 72%
“…In the plasma of type 2 diabetes patients after long-term use of sulfonylurea, the proportion of proinsulin and other non-mature forms to mature insulin is increased (24,25); the rapid and overloaded insulin processing exhausted islets and possibly induce ER stress. In the present study, we suggested that chronic exposure to glibenclamide, one of the commonly used sulfonylurea compounds, induced ER stress and finally brought on β-cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Though United Kingdom Prospective Diabetes Study (28) found that the loss of E-cell function was not unique for sulfonylureas but occurred at the same rate of decline in type 2 diabetic patients on metformin or on conventional treatment, it was found recently that in newly diagnosed diabetic patients, Endoplasmic Reticulum Stress in Diabetes sulfonylureas has higher therapeutic failure rate and faster loss of E-cell function than metformin and rosiglitazone (29). In fact, many studies have reported that chronic use of sulfonylureas could increase the level of proinsulin (misfolded product of ER in E-cells) in plasma of type 2 diabetes, which means that disequilibrium between ER load and folding capacity deteriorated in E-cells (30,31). A multicentre, randomised trial also found that early intensive insulin therapy in patients with newly diagnosed type 2 diabetes has favorable outcomes on recovery and maintenance of E-cell function compared with treatment with oral hypoglycemic agents (32).…”
Section: Er Stress and Secondary Sulfonylurea Failure In Type 2 Diabetesmentioning
confidence: 99%